Synthesis and bioactivity studies of coumarin and its derivatives - Wong, Kok Tong (2013)
Coumarin is a naturally occurring compounds being present in several plants and also can be produced through organic synthetic reactions. In this study, substituted coumarins of 3-acetylcoumarin, 3-acetyl-7-(diethylamino)coumarin, 7-(diethylamino)-3-(1-oxobutyl)coumarin, 3-oxobutyl-3H-naphtho[2,1-b]pyran-2- one, 6-bromo-3-(1-oxobutyl)coumarin and 8-methoxy-3-(1-oxobutyl)coumarin were synthesized via Knoevenagel condensation reaction of respective 2-hydroxybenzaldehyde derivatives with active methylene group from ethyl acetate or ethyl butyrylacetate under basic condition. Meanwhile, 7-hydroxy-4-methylcoumarin, 4-methyl-2H-benzo[h]chromen-2-one, 7-hydroxy-4,8-dimethylcoumarin, 7-hydroxy- 4-propylcoumarin, 4-propyl-2H-benzo[h]chromen-2-one, 7-hydroxy-8-methyl-4- propylcoumarin and 7,8-dihydroxy-4-propylcoumarin were prepared through Pechmann condensation reaction by the condensation of respective substituted phenol and ß-keto-ester in the presence of sulphuric acid as a catalyst. Futher methylation reaction on 7-hydroxy-4-methylcoumarin with iodomethane catalysed by K2CO3 gave 7-methoxy-4-methylcoumarin. Modification of hydroxyl group of 7,8-dihydroxy-4-propylcoumarin using butyric anhydride and dry pyridine yielded 7,8-bis-(1-oxobutoxy)-4-propylcoumarin. In addition, 7-hydroxy-4,8-dimethylcoumarin was converted to 7-benzyloxy-4,8-dimethylcoumarin through reaction of benzyl chloride in dry acetone. In addition, 7,8-methylenedioxy-4-propylcoumarin undergoes Williamson etherification reaction which involved SN2 mechanism between secondary alkyl halide with potassium salt of a phenoxide. All compounds were characterized by spectroscopic techniques using infrared (IR), proton and carbon nuclear magnetic resonance (1H and 13C NMR), and mass spectrometry (MS). The synthesized compounds were tested for their antioxidant and antibacterial activities. It was found that the hydroxylated coumarin derivatives of 7,8-dihydroxy-4-propylcoumarin were tested positive towards 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay with IC50 value of 4.09 ?g/mL while other hydroxylated compounds were inactive. The antibacterial activity show that 6-bromo- 3-(1-oxobutyl)coumarin exhibited as strong antibacterial agent against B. subtilis bacteria with MIC value 56.25 ?g/mL. 7,8-Methylenedioxy-4-propylcoumarin showed strong activity to all Gram-positive bacteria.